Comparative analysis of motor skills for boxers with different competitive level of the competition success in the Republic of North Macedonia - Kalach, R.; Georgiev, G.; Gontarev, S. (Journal Pedagogical Almanac, 2020)
This research was conducted on a selected sample of 87 male respondents, boxers at the age of 18 to 33 years with the aim to determine if there are some differences in motor skills between boxers with different levels of competitive success. The sample is divided into three sub-samples according to the competitive success as follows: I category of 20 boxers who achieved the best sport results in the boxing from the Republic of North Macedonia, participating in the World, European and other international tournaments, II category of 25 of boxers who participated in international tournaments, domestic tournaments, Republican league and state championships and III category of 42 boxers who participated in international tournaments, domestic tournaments, Republican league and state championships but had not achieved significant sport results. For assessment of the motor skills a system of 21 motor tests was applied. The differences in the general motor tests between the boxers with different levels of competitive success are determined by the covariance analysis with the partition of weight and height. Based on the results it can be concluded that the significant basic motor skills which differentiate the boxers with different levels of competitive success is the coordination - agility, the strength of the muscles of the arms and the shoulder area, the speed of the frequency of upper extremities, the explosive strength of upper and lower extremities and the placement precision. The results from this research can help the coaches to properly plan and program the work with the boxers during the training process